Penerapan Model Pembelajaran Inquiri Terbimbing Terhadap Hasil Belajar Pada Materi Hukum Newton Kelas X - Resto Reswanto; Hadma Yuliani; Nur Inayah Syar (Kappa Journal, 2021)
This study was based on the lack of student learning outcomes due to the low variation in the learning model. This study aims to examine (1) Management of learning using inkuiri learning model guided in newton law material class X. (2) Significant influence before and after the implementation of the inkuiri learning model is guided to the learning outcomes in newton law material class X. This research uses quantitative approach and this type of research uses Pre-Experimental design in this design there is no control group to compare with the experimental group and with "One Group Pretest – Posttest Design". Instruments used in the form of observation sheets of learning management, tests of cognitive learning results, observation sheets affective and psychomotor. The population in this study took grade X science students in semester 2 at MA Muslimat NU Palangkaraya by sampling using saturation sampling techniques or saturated samples then the entire population was sampled. The results showed that (1) The management of learning using inquiri guided with an average value of 3.4 is quite good status. (2) The influence of guided inquiri learning models on learning outcomes with a significant value of 0.00 < 0.05.